Women with mild fasting hyperglycemia in early pregnancy have more neonatal intensive care admissions - Benhalima, Katrien (J Clin Endocrinol Metab, 2020)
AIMS: To determine impact of mild fasting hyperglycemia in early pregnancy [fasting plasma glucose (FPG) (5.1-5.5mmol/l)] on pregnancy outcomes. METHODS: We measured FPG at 11.9 ±1.8 weeks in 2006 women from a prospective cohort study. Women with FPG ≥5.6mmol/l (19) received treatment and were excluded from further analyses. 1838 women with FPG <5.6mmol/l received a 75g oral glucose tolerance test (OGTT) between 24-28 weeks of pregnancy. RESULTS: Of all participants, 78 (4.2%) had FPG 5.1-5.5mmol/l in early pregnancy, of which 49 had a normal OGTT later in pregnancy [high fasting normal glucose tolerance (NGT) group]. Compared to the NGT group with FPG <5.1 mmol/l in early pregnancy (low fasting NGT group, n=1560), the high fasting NGT group had a higher BMI, higher insulin resistance with more impaired insulin secretion and higher FPG and 30 min glucose levels on the OGTT. The admission rate to neonatal intensive care unit (NICU) was significantly higher in the high fasting NGT group compared to the low fasting NGT group [20.4% (10) vs. 9.3% (143), p=0.009], with no difference in duration (7.0±8.6 vs. 8.4±14.3 days, p= 0.849) or indication for NICU admission between both groups. The admission rate to NICU remained significantly higher [OR 2.47 (95% CI 1.18-5.19), p=0.017] after adjustment for age, BMI and glucose levels at the OGTT. CONCLUSIONS: When provision of an OGTT is limited such as in the Covid-19 pandemic, using FPG in early pregnancy could be an easy alternative to determine who is at increased risk for adverse pregnancy outcomes.